1998
DOI: 10.1007/bf02447144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vagal stimulation on cardiac rhythm in rats under blockade of β-adrenoreceptors by obsidan

Abstract: Obsidan induced age-dependent bradycardia in intact rats and in rats with chemical sympathetic denervation. Subsequent vagal stimulation produced further decrease in heart rate. Administration of atropine to obsidan-treated rats increased heart rate. Key Words: rat; vagus; chemical sympathetic denervation; cardiac rhythm; obsidanThe degree of postvagotomy tachycardia varies in different species [7]. In small rodents the vagal tone is the lowest [5]. Inhibition of cardiotropic adrenergic influences produces onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It was established that irrespective of animal age the heart rate remained unchanged under conditions of total adreno-and cholinergic blockade of the heart. Stroke volume under conditions of total adreno-and cholinergic blockade increased with age.Laboratory of Physiology of Physical Training, Tatar State Humani tarian Pedagogical University, Kazan Adrenergic and cholinergic mechanisms regulating pumping function of the heart during ontogeny under conditions of muscle training and hypokinesia are extensively studied [2][3][4][5][6]. At the same time, the degree of changes in functional state of adrenergic and cholinergic receptors during physical exercise, and changes in heart rate (HR), stroke volume (SV), and cardiac output (CO) at rest and under the effect of muscle training and hypokinesia requires further investigation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was established that irrespective of animal age the heart rate remained unchanged under conditions of total adreno-and cholinergic blockade of the heart. Stroke volume under conditions of total adreno-and cholinergic blockade increased with age.Laboratory of Physiology of Physical Training, Tatar State Humani tarian Pedagogical University, Kazan Adrenergic and cholinergic mechanisms regulating pumping function of the heart during ontogeny under conditions of muscle training and hypokinesia are extensively studied [2][3][4][5][6]. At the same time, the degree of changes in functional state of adrenergic and cholinergic receptors during physical exercise, and changes in heart rate (HR), stroke volume (SV), and cardiac output (CO) at rest and under the effect of muscle training and hypokinesia requires further investigation.…”
mentioning
confidence: 99%
“…Adrenergic and cholinergic mechanisms regulating pumping function of the heart during ontogeny under conditions of muscle training and hypokinesia are extensively studied [2][3][4][5][6]. At the same time, the degree of changes in functional state of adrenergic and cholinergic receptors during physical exercise, and changes in heart rate (HR), stroke volume (SV), and cardiac output (CO) at rest and under the effect of muscle training and hypokinesia requires further investigation.…”
mentioning
confidence: 99%
“…Published data show that parasympathetic regulatory influences on the heart are realized via muscarinic M 2 AChR [10]. Recent studies indicate that muscarinic M 1 and M 3 AChR play a role in cholinergic regulatory influences on the heart [4,11,13,14].Study of vagal regulation of the heart in laboratory animals revealed significant interstrain differences in the mechanisms of cardiac rhythm regulation in rats [1,3,7]. The possibility of immediate and tonic vagal inhibition of cardiac activity in rats was hypothesized [2].…”
mentioning
confidence: 97%
“…Study of vagal regulation of the heart in laboratory animals revealed significant interstrain differences in the mechanisms of cardiac rhythm regulation in rats [1,3,7]. The possibility of immediate and tonic vagal inhibition of cardiac activity in rats was hypothesized [2].…”
mentioning
confidence: 99%
“…Rats sympathectomized with guanethidine in the early period of life served as the model to study functional activity of the sympathetic nervous system. Most studies were devoted to estimate the effect of sympathectomy on HR [3,4]. Little is known about the response of HR and stroke volume (SV) in sympathectomized animals to various factors [1,9,10].…”
mentioning
confidence: 99%